Madrasah Headmaster Performance Strategy in Madrasah Al-Washliyah 22 Tembung - Ahmad Husin Siregar; Yusuf Hadijaya (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
This study is to describe how the Strategy for Improving the Performance of Al-Washliyah Private Madrasah 22 Tembung. In Improving Performance of Al-Washliyah 22 Tembung. Madrasa Headmaster is a way to improve the quality of education and achieve educational goals. This type of research conducted is a type of qualitative research with naturalistic. Research data collection was obtained by collection techniques, interviews and documentation studies. The step of data analysis is to collect data, reduce data, present data and then collect data. To retrieve the validity data, a test of creativeness, transferability, dependability and confirmability was carried out. The findings of this study discussed three findings that discussed 1) Strategy for Improving the Performance of Madrasah Head in Al-Washliyah Madrasah 22 Tembung. 2) Madrasah Superintendent and Principal Development Policy at Al-Washliyah Madrasah 22 Tembung in Mapenda Area of ​​the Provincial Ministry of Religion Office. 3) Implementation of Strategy Management for Madrasah Principals in Al-Washliyah Madrasah 22 Tembung. The results of this study were concluded as a Strategy for Improving the Performance of Headmaster at Al-Washliyah Madrasah 22 Tembung performed well and certainly there were still deficiencies that were not properly used properly.